The Skin Microbiome and Its Role in Psoriasis: A Review - Celoria V; Rosset F; Pala V; Dapavo P; Ribero S; Quaglino P; Mastorino L (Dove Medical Press, 2023)
Valentina Celoria,* Francois Rosset,* Valentina Pala, Paolo Dapavo, Simone Ribero, Pietro Quaglino, Luca Mastorino Dermatologic Clinic, Department of Medical Sciences, University of Turin, Turin, Italy*These authors contributed equally to this workCorrespondence: Valentina Celoria, Dermatologic Clinic, Department of Medical Sciences, University of Turin, Turin, Italy, Email valentina.celoria@edu.unito.itAbstract: The skin microbiome is made of various microorganisms, most of which have the function of protecting individuals from harmful pathogens, and they are involved in innate and adaptive immune responses. The skin acts as a physical and immunological barrier against external stimuli, including pathogens and physical damage. Changes in the composition of the skin microbiome can trigger inflammatory processes leading to inflammatory skin diseases in susceptible individuals. Psoriasis (PsO) is a chronic inflammatory disease with a multifactorial etiology, where breakdown of immune tolerance to cutaneous microorganisms is implicated in its pathogenesis. Dysregulation of the microbiome due to genetic and environmental factors plays a significant role in the development of psoriatic disease. Dermatologic conditions such as atopic dermatitis, acne, psoriasis, and rosacea have been associated with intestinal dysbiosis. The skin microbiota composition is crucial for the development of appropriate immune responses, and alterations in the skin microbiome can contribute to changes in physiology and susceptibility to skin diseases or inflammatory conditions. Understanding the microbial settlement of the skin and the network of interactions that occur throughout life is essential for comprehending the pathogenesis of skin diseases and developing innovative treatments. With this article we tried to explore the relationship between the human microbiome and psoriatic disease, shedding light on the functions of the microbiome and the inflammatory disease processes to identify additional therapeutic targets. This review aims to highlight the relationship between skin and gut microbiome functions and inflammatory processes in skin psoriasis and psoriatic arthritis (PsA). The goal is to facilitate future studies on the skin microbiome to identify potential novel therapies for patients with psoriatic disease.Keywords: psoriasis, skin microbiome, new therapies, gut microbiome, molecular precision medicines, next generation treatments